Measuring and Improving Service Quality in The Context of a Higher Educational Institution: Human Science Students’ Perceptions at Sariputta College, Muse, Northern Shan State, Myanmar (International Journal of Applied Research in Management and Economics, 2020)
The main purpose of this research is to determine the current situation of the five SERVQUAL dimensions of service quality instrumentation: tangibles, reliability, responsiveness, assurance, and empathy. These dimensions are used shed light on the most meaningful service features. This study has used a service quality model from an undergraduate student’s point of view. It aimed to explore and evaluate current service attitude and quality at the college. A mixed methodology was conducted on human science program students at Sariputta College in 2019. The students were selected through printed questionnaires using the purposive sampling method. The students’ attitude towards educational service quality was measured through a questionnaire that was designed according to service quality instrumentation based on the five dimensions. The quantitative data was analyzed by SPSS software through the Alpha Test, Descriptive Statistics, Multiple Linear Regression and one-way ANOVA and also by qualitative analysis. The results revealed the lowest recorded service quality gaps belonged to the tangible (-.042) and the highest belonged to the empathy (.007) dimensions respectively. Moreover, a significant number of students felt that Sariputta College does not have an up-to-date curriculum and the highest number felt that the staff of Sariputta College are friendly towards them. Another factor that emerged concerned the facilities and equipment which need to be upgraded in order to reduce the undergraduate students’ negative attitude towards higher education at the college. Thus, it is recommended that services are provided based on students’ needs and suggestions.